1999
DOI: 10.1007/s002620050592
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor in malignant pleural effusion associated with lung cancer

Abstract: The presence of vascular endothelial growth factor (VEGF) was examined by enzyme immunoassay in 60 cytology-documented malignant pleural effusions associated with primary lung cancer and 51 other benign and malignant pleural effusions. Exudative pleural effusions contained significantly higher amounts of VEGF than transudative pleural effusions. Among exudative pleural effusions, levels of VEGF in malignant pleural effusions associated with lung cancer were significantly higher than those of benign exudative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 23 publications
5
58
0
8
Order By: Relevance
“…In agreement with previous reports, the current study found that VEGF levels in PE and serum are significantly higher in malignant than in benign effusions. But VEGF was not a good discriminator because of the considerable overlap between the two groups, this was also consistent with former investigations (Yanagawa et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with previous reports, the current study found that VEGF levels in PE and serum are significantly higher in malignant than in benign effusions. But VEGF was not a good discriminator because of the considerable overlap between the two groups, this was also consistent with former investigations (Yanagawa et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Elevated levels of VEGF produced by tumor cells, mesothelial cells, and infiltrating immune cells result in increased vascular permeability, cancer cell transmigration, and angiogenesis (Zebrowski et al, 1999;Cao et al, 2013;Dong et al, 2013;Song et al, 2013). Different authors have highlighted the role played by VEGF in the accumulation of exudative PE, especially that of MPE associated with lung cancer (Yanagawa et al, 1999). A few studies (Sack et al, 2005;Zhang et al, 2012;Zhou et al, 2009;Koniari et al, 2011;Yanagawa et al, 1999;Ziora et al, 2002;Fiorelli et al, 2011) have suggested that high VEGF levels in both serum and PE might be considered predictive of malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VEGF is also known as vascular permeability factor, and can induce vascular leakage and may be involved brain edema (Ferrara et al, 2003). Malignant pleural effusions from lung cancer have high levels of VEGF, and VEGF secretion has also been associated with the development of ascites (Senger et al, 1983;Yanagawa et al, 1999;Yano et al, 2000a). The direct role VEGF has in angiogenesis and other malignant processes made it an attractive target for the development of new therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%